The Radicalism of the Enlightenment. An Introduction to the Special Edition (Diametros, 2014)
This brief “Introduction” to the volume discusses the general idea of the special edition of the journal, which is dedicated to the radicalism of the Enlightenment in the context of Jonathan Israel’s recent work on the Enlightenment, and highlights the topics of the articles contained in the edition.
Keywords: Enlightenment; radical Enlightenment; moderate Enlightenment; Spinoza; revolution; European consciousness; liberal democracy